The Risk of Work Posture Did Not Affect on Worker’s Disability Index with Low Back Pain Complaints in PT Muroco Jember - Anis Rahmawati; Yohanes Sudarmanto; Muhammad Hasan (Faculty of Medicine, University of Jember, 2019)
The existence of various industrial centers in Jember Regency has an impact on the high absorption of labor coming from the local community, because most of the production activities are still done by using the power / physical strength of man. Low back pain (LBP) is one of the symptoms of musculoskeletal pain in the lower back, not a disease or diagnosis for a disease. The high risk factor of LBP complaints occurring in industrial workers is the work posture. Patients with chronic LBP complaints may experience affective disorders such as depression and psychosomatic disorders that will lead to a poorer prognosis, while also often experiencing disabilities that implicate the quality of life of patients. This study aims to determine the risk of work posture on worker’s disability index with low back pain complaints in PT Muroco Jember. The type of this research is observational analytic with cross sectional research design which conducted on 31 workers of PT Muroco which fulfill the criteria of inclusion and exclusion. The risk of work posture was obtained by employee observation and completion of the modified quick exposure check questionnaire while the disability index was obtained by filling the modified oswestry low back pain disability questionnaire. The result of the Gamma correlation between the two variables is p = 0,135. It shows that there is no correlation between risk of work posture and worker’s disability index with low back pain complaint in PT Muroco Jember.